Preteklost za sedanjost - Vodopivec, Nina (Monitor ISH, 2005)
The past for the present: the social memory of textile workers. The paper examines how the Slovene textile workers' views of the past and their current perception of their working and living space have been affected by the social and political changes since 1991, as well as by the resulting changes in the frames of reference. The central question is how the notions of group identity are shaped in the memory. An exploration of the ways in which people control their memories of past events may shed important new light on the contemporary social dynamics and identification processes. The paper, focusingon the everyday life of textile workers, calls attention to the contradictions and ambivalence of post-Socialist recollections.
Keywords: socialni spomin; socialism; socializem; delavke; delavci; tekstilna industrija; pripadnost; Slovenia; Slovenija